G-continued fractions for basic hypergeometric functions II - Bowman, Douglas; Choi, Geumlan (Journal of mathematical analysis and applications, 2003)
In this paper we apply a modification of a generalized Pringsheim's theorem to obtain a G-continued fraction expansion for the quotient of two contiguous basic hypergeometric functions in arbitrarily many variables. As an application we obtain a G-continued fraction extension of the Rogers–Ramanujan continued fraction.